The runaway heiress - Tilly, Meg (Jove, 2021)
With a new name and fake ID papers, Sarah Patterson, on the run from her violent estranged husband--a police lieutenant--takes a job working with Hollywood's golden boy director who, as their bond deepens, attempts to keep Sarah out of harm's way.